1991
DOI: 10.1007/bf00348161
|View full text |Cite
|
Sign up to set email alerts
|

Total reflection X-ray fluorescence spectrometry for quantitative surface and layer analysis

Abstract: Abstract. Measurements of X-ray fluorescence spectra versus grazing incident angles provide information on elemental composition as well as density and thickness of near surface layers. Calculations of fluorescence intensities are presented, which are used for the evaluation of data obtained by total reflection X-ray fluorescence (TXRF) spectrometry. The calculation is based on a matrix formalism to account for standing wave phenomena due to transmission and reflection in layered material. For the determinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…The resulting values are plotted versus angle to give the intensity profiles. From these profiles, the respective sample parameters (particle size, layer thickness) can be evaluated by an iterative fitting procedure on the basis of modeling calculations using the modulated intensity distribution above the reflector as an extremely fine dynamic ruler [11,21,[39][40][41].…”
Section: Trendsmentioning
confidence: 99%
“…The resulting values are plotted versus angle to give the intensity profiles. From these profiles, the respective sample parameters (particle size, layer thickness) can be evaluated by an iterative fitting procedure on the basis of modeling calculations using the modulated intensity distribution above the reflector as an extremely fine dynamic ruler [11,21,[39][40][41].…”
Section: Trendsmentioning
confidence: 99%
“…The angle-dependent fluorescence intensities were interpreted using calculations or fittings obtained with the dedicated software developed by the GKSS research center (Geesthacht, Germany). 17,19 TOF-SIMS depth profiles were obtained using a commercial instrument (Iontof-IV). The HfO2 layer was sputtered using a Xe + beam at an energy of 500 eV and a flux of 7 × 10 13 at/cm 2 (current of 20 mA over a raster of 400 × 400 µm 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…If the layer is sufficiently thick, the density and thickness can also be determined. The method is based on calculating the angle dependent fluorescence intensities from layered samples, as developed simultaneously by Weisbrod et al and de Boer et al 17,18 The Fresnel relations are used to account for standing-wave phenomena due to transmission and reflection in these samples. For quantification, the model makes additional use of the fundamental parameter technique to account for absorption and enhancement effects of the fluorescent radiation.…”
Section: N||-oh (S) + Hfcl4 (G) → (||-O-)nhfcl4-n (S) + Nhcl (G) (1amentioning
confidence: 99%
“…11,12 The various advantages of GI-XRF technique over the other commonly used techniques of thin film analysis, such as X-ray reflectivity or secondary ion mass spectrometry, have been described by several workers. [13][14][15] Apart from analysis of thin layer and adsorbed particulate matter on a substrate, Barbee and Warburton 16 applied the GI-XRF technique to investigate periodic multilayer structures. They showed that X-ray standing wave (XSW) effects occur in multilayer Bragg peak regions as in perfect crystals.…”
Section: Introductionmentioning
confidence: 99%